HCAS/CSE1L regulates RAD51 distribution and focus formation for homologous recombinational repair. (30th June 2015) - Okimoto, Satoshi; Sun, Jiying; Fukuto, Atsuhiko; Horikoshi, Yasunori; Matsuda, Shun; Matsuda, Tomonari; Ikura, Masae; Ikura, Tsuyoshi; Machida, Shinichi; Kurumizaka, Hitoshi; Miyamoto, Yoichi; Oka, Masahiro; et al.
<x xml:space="preserve">Abstract</x> Homologous recombinational repair (HR) is one of the major repair systems for DNA double‐strand breaks. RAD51 is a key molecule in HR, and the RAD51 concentration in the cell nucleus increases after DNA damage induction. However, the mechanism that regulates the intracellular distribution of RAD51 is still unclear. Here, we show that hCAS/CSE1L associates with RAD51 in human cells. We found that hCAS/CSE1L negatively regulates the nuclear protein level of RAD51 under normal conditions. hCAS/CSE1L is also required to repress the DNA damage‐induced focus formation of RAD51. Moreover, we show that hCAS/CSE1L plays roles in the regulation of the HR activity and in chromosome stability. These findings suggest that hCAS/CSE1L is responsible for controlling the HR activity by directly interacting with RAD51.